Specialty preferences of 1(st) year medical students in a Saudi Medical School – Factors affecting these choices and the influence of gender - Kaliyadan, Feroze (Avicenna J Med, 2015)
BACKGROUND AND AIMS: In recent years there has been a growing appreciation of the issues of career preference in medicine as it affects student learning and academic performance. Various factors influence the specialty choices of medical students. Some specialties tend to attract students more than others. One possible consequence of this would be a mismatch between health needs and specialist numbers in the region. This study investigated the career preferences of 1(st) year medical students in a Saudi medical school and to assess factors affecting these choices. MATERIALS AND METHODS: The study was a cross-sectional survey carried out on the 1(st) year undergraduate students in the college of medicine, King Faisal University, Saudi Arabia. A total of 109 students (57 female and 52 males) responded to the questionnaire which was initially administered to all the students of the 1(st) year – A total of 120 students (response rate was 90.8%). A mixed method approach was used and qualitative data from open-ended questions were analyzed based on thematic analysis. RESULTS: The top choices were general surgery, internal medicine, and pediatrics. Among female students; the top specialty choices were: General surgery (23%), pediatrics (18%), and dermatology (15%). Among the male students; the top choices were: General surgery (54%) and internal medicine (23%). Of the total, 57% of the students agreed or strongly agreed that primary aptitude was the main factor affecting the choice. Only 31% felt that there was a significant influence of role model, 48% felt that the advice of others – peers and family, would be a factor influencing their choices, and 53% agreed that specialty choice would influence their future learning patterns. Males were more likely to choose a specialty based on actual aptitude for the specialty, financial rewards, and scope for research; and this gender difference was statistically significant. CONCLUSION: Surgery was the top-choice in both genders. Other popular choices included internal medicine, pediatrics, and dermatology. Important factors affecting these choices included – primary aptitude, advice of peers, reputation, financial rewards, and the challenge involved.